CLINICAL FEATURES OF BEHAVIORAL DISORDERS RELATING TO AMPHETAMINE TYPE SUBSTANCES USE (Vietnam Journal of Community Medicine, 2020)
The symptoms of behavioral disturbances in patients with psychosis caused by the use of amphetamine-type substances (ATS) are diverse, leading to difficulties in diagnosis and treatment. Purposes: To describe the clinical features of behavioral disorders relating to ATS use. Objects and research methods: Study on case clusters of 74 patients with inpatient mental disorders by using ATS at the National Institute of Mental Health, Central Mental Hospital 1, Psychiatric Hospital Ha Noi from September 2019 to August 2020. Results: Common symptoms relating to ATS use are hyperactive behavior (54%), agitated behavior (62%), behavior dominated by delusions, hallucinations (47.3%). There was a relationship between hyperactive behavior, impulsive behavior, aggressive behavior, and property destruction and agitation (p 0.05).
Keywords: Behavioral disorders, ATS use